Implantação dos princípios e ferramentas da lean construction: um estudo de caso em um condomínio residencial multifamiliar na cidade de Maringá-PR - Santos, Everton de Britto (2021)
The construction industry is known as one of the segments with the lowest productivity when compared to the other sectors. The criticality of this index indicates that one of the main reasons is the lack of management of the processes during the entire life cycle of the construction project. As an alternative to the traditional management model, there is the philosophy called Lean Construction, an adaptation of the principles and concepts disseminated in the automobile industry for civil construction. Given this scenario, the present study aims to implement innovation in process and measure the results from the use of lean tools and methodologies in a multifamily residential development in the city of Maringá - PR. The insertion of continuous improvement processes was present in different stages during the development of this research, classified as qualitative. As a result, there is an increase in the PPC% of 26.63% and 24% of the IRR% considering the average between the month of May and September 2020. With the implementation of the Last Planner System, it was possible to show evident benefits in the planning and in the continuous improvement processes. During the Week Work Plan meetings, the relationship between the IRR% and the PPC% was highlighted, that is, the more efficient the process of removing restrictions, the greater the fulfillment of the plan. With the implementation of Kaizen forms in the appearance of the defect, in the weekly planning for treatment of the main reasons for the variation of the plan and also in the process of laying ceramic blocks masonry, in which it obtained a productivity increase of 53.38% between the first and the seventh floor. Through the Unit Production Ratio, it was possible to identify the real productivity of the activities, this data source was used to refine the planning of new projects and proved by means of control charts the stability of the production processes. The reduction in the lead time of the project was also contacted. By comparing the real and planned S curve, it was found that in October 2020 the difference was 8.97% between the real and the planned advance. Finally, the implementation of these concepts in the production processes of this enterprise provided increased productivity, improved quality, integration and increased knowledge of the teams and, consequently, greater added value to the final customer.